Using remote sensing techniques for rural development planning in Kenya: a study in Meru district - Gibbon, Hugh (1987)
The thesis sets out to examine the utility of remote sensing techniques in helping to define recommendation domains relatively homogeneous agricultural areas - to act as foci for agricultural development planning in lower Meru, Kenya.